2019
DOI: 10.1007/s13127-019-00417-z
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive phylogeographic study of Arion vulgaris Moquin-Tandon, 1855 (Gastropoda: Pulmonata: Arionidae) in Europe

Abstract: Arion vulgaris Moquin-Tandon, 1855 is regarded as one of the 100 most invasive species in Europe. The native distribution range of this species is uncertain, but for many years, the Iberian Peninsula has been considered as the area of origin. However, recent studies indicate that A. vulgaris probably originated from France. We have investigated the genetic structure of 33 European populations (Poland, Norway, Germany, France, Denmark, Switzerland) of this slug, based on two molecular markers, mitochondrial cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…However, the very similar external appearance with other closely related native large arionids as well as hybrid species between A. vulgaris, A. ater and A. rufus [14][15][16], might cause the misidentification of A. vulgaris, obscure the specimen records, and make it difficult to trace its origin and monitoring the spread only by morphological identification [17,18]. Controversially, recent studies based on the genetic diversity patterns of mitochondrial and nuclear loci suggested that A. vulgaris is native in central Europe rather than alien/invasive while probably invasive in other parts of Europe [19][20][21]. In either case, it is undeniable that its outstanding adaptive success, the mass occurrences and consequent pest in the last 40-50 years and the reason behind is worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…However, the very similar external appearance with other closely related native large arionids as well as hybrid species between A. vulgaris, A. ater and A. rufus [14][15][16], might cause the misidentification of A. vulgaris, obscure the specimen records, and make it difficult to trace its origin and monitoring the spread only by morphological identification [17,18]. Controversially, recent studies based on the genetic diversity patterns of mitochondrial and nuclear loci suggested that A. vulgaris is native in central Europe rather than alien/invasive while probably invasive in other parts of Europe [19][20][21]. In either case, it is undeniable that its outstanding adaptive success, the mass occurrences and consequent pest in the last 40-50 years and the reason behind is worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of both species was confirmed thanks to molecular analysis [95,98]. On the other hand, A. vulgaris, commonly named 'Spanish slug', is a wide distributed species with a high expansive and invasive character [9,104]. Although its origin is not clear, it could be native from Central Europe [104,105].…”
Section: Arion Lusitanicus Auct Non Mabille 1868/arion Vulgaris Moquin-tandon 1855mentioning
confidence: 91%
“…On the other hand, A. vulgaris, commonly named 'Spanish slug', is a wide distributed species with a high expansive and invasive character [9,104]. Although its origin is not clear, it could be native from Central Europe [104,105]. Thus, all the records of this species in Asturias must be reviewed [25,70,80,88,102] because only A. lusitanicus was apparently recorded.…”
Section: Arion Lusitanicus Auct Non Mabille 1868/arion Vulgaris Moquin-tandon 1855mentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe the only mollusc among the 100 worst invasive alien species is the Spanish slug Arion vulgaris , formerly known as A. lusitanicus ( Rabitsch, 2006 ). The exact area of origin for A. vulgaris is still not definitely determined ( Pfenninger et al, 2014 ; Zemanova, Knop & Heckel, 2014 ) and a recent study suspects it to be in France and Western Germany ( Zając et al, 2020 ). Over the last decades, however, the slug has spread over large parts of Europe ( Engelke et al, 2011 ; Kozłowski & Kozłowski, 2011 ; Hatteland et al, 2013 ; Papureanu, Reise & Varga, 2014 ; Balashov et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%